Inequality and Education Subsidies in General Equilibrium Growth Model for a Small Open Economy - Zhang, Wei-Bin (Asian Journal of Economic Modelling, 2018)
The paper is concerned with dynamic interactions between physical capital, human capital, income and wealth inequalities between different households with government subsidy to education. The model is developed on the basis of Solow-Uzawa’s neoclassical growth theory, Uzawa-Lucas model, Arrow’s learning by doing, Zhang’s creative leisure, and Walrasian general equilibrium theory. The capital accumulation and economic structure are based on the neoclassical growth theory. The human capital accumulation is due to Uzawa’s education, Arrow’s learning by doing, and Zhang’s creative leisure. The model explains income and wealth inequality between groups with government education subsidy policy in a small-open economy. The model reveals a complicated nonlinear dynamic interdependence between wealth accumulation, human capital accumulation, economic structural change, division of labor, and time distribution under perfect competition and government education subsidy policy. We simulate the economy composed of three groups of households. We carry out comparative dynamic analysis and demonstrated how a change in a parameter affects the path of economic growth.